7(m-5)=15(3-m)+2m

Simple and best practice solution for 7(m-5)=15(3-m)+2m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(m-5)=15(3-m)+2m equation:


Simplifying
7(m + -5) = 15(3 + -1m) + 2m

Reorder the terms:
7(-5 + m) = 15(3 + -1m) + 2m
(-5 * 7 + m * 7) = 15(3 + -1m) + 2m
(-35 + 7m) = 15(3 + -1m) + 2m
-35 + 7m = (3 * 15 + -1m * 15) + 2m
-35 + 7m = (45 + -15m) + 2m

Combine like terms: -15m + 2m = -13m
-35 + 7m = 45 + -13m

Solving
-35 + 7m = 45 + -13m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '13m' to each side of the equation.
-35 + 7m + 13m = 45 + -13m + 13m

Combine like terms: 7m + 13m = 20m
-35 + 20m = 45 + -13m + 13m

Combine like terms: -13m + 13m = 0
-35 + 20m = 45 + 0
-35 + 20m = 45

Add '35' to each side of the equation.
-35 + 35 + 20m = 45 + 35

Combine like terms: -35 + 35 = 0
0 + 20m = 45 + 35
20m = 45 + 35

Combine like terms: 45 + 35 = 80
20m = 80

Divide each side by '20'.
m = 4

Simplifying
m = 4

See similar equations:

| 1550=700+85(x) | | 1500=700+85(x) | | y-30=-25 | | 15x^2-66x+24=0 | | y=1000+25(10) | | 11-2x=5(x-5)+15 | | 28x^3-39x^2+12x-1=0 | | 9+5s-2=7-2s | | 2L-6=12-L | | x+(x+1)=77 | | 8(-24)+3=-48 | | 8x+3=-48 | | 15x^2-66x+24x=0 | | p=2(98)+2(102) | | 4x^2+64+220=0 | | 5x^2-3=27 | | 4x^2+20x=200 | | 18w-33=7w | | 3w^2+27w+54=0 | | 96=-16t^2+192t | | 21x^2-588=63x | | 16t^2-192t+96=0 | | x-32=530 | | 530=x+22 | | 10x+8-4=9x-4 | | 4x+3=7x+3 | | 16x^2+57x+49=x | | 3p^2-12q^2=0 | | 530=22-32+3x | | 7+4s-6=8s+5-3s | | 4s^2=s+1 | | -(8y+4)-(-7y-7)=-1 |

Equations solver categories